INSOLVENCY LAW IN THE REPUBLIC OF UZBEKISTAN: HISTORICAL AND COMPARATIVE ANALYSIS (TSUL LEGAL REPORT, 2026)
This article studied and analyzed the history of insolvency law of Uzbekistan, issues of protection of the entrepreneurs’ rights, restoring solvency of the debtor, and satisfaction of creditors’ claims with the use of insolvency procedures in accordance with the bankruptcy law of the Republic of Uzbekistan. In addition, when determining the signs of insolvency, it was analyzed that monetary obligations and debts on mandatory payments should be taken into account, and claims arising from labor relations should not be grounds for initiating bankruptcy proceedings. Particular attention was paid to the objectives of the credit policy when establishing insolvency regimes, based on two goals - fair distribution of risks and maximizing the value of the debtor’s assets. The models of insolvency regulation are analyzed using the example of the countries of Europe and the USA; their experience is compared with the practice of Uzbekistan. In particular, it has been established that rehabilitation norms appeared in US legislation and were subsequently used as a model in European countries, and the legislation of many countries is currently improving its legislation on the rehabilitation of the debtor. Analytical conclusions, ideas, and recommendations were also developed on the need to develop the concept of insolvency in Uzbekistan and the priorities that should be reflected in it.